Jean-Baptiste Debret E O Pano De Boca De 1822: O Lugar Da Pintura De História No Teatro Da Corte - Camargo, Marcela Dantas [UNIFESP] (2017)
This research is focused on the main curtain made by Jean-Baptiste Debret for the staging of the coronation of Peter I, which took place in the Court Theatre in 1822, and its connections with history painting. It’s our intention to articulate it to the political agenda and present the theatrical room as the place for depictions understood as history painting, to which Debret devoted himself in France as a disciple to Jacques-Louis David. We approach the narrative and all the elements proposed by the artist in this work to understand his goals in glorifying the Empire of Peter I. We revisit the decoration created by Debret for the theater, as it also was his workplace, analyzing his connections to monumental painting, as he used before to hallow Napoleon, now dedicated to exalt Peter I. This research proposes an understanding of the main curtain as the consecration of history painting and the portrayal of the power in a place that transcends the stage for theatrical plays, embodying the role of a locus for social and political debate during the events of the independence and construction of the Brazilian nation.